RETRACTED: Environmental and economic efficiency of the implementation of production modernization programs - Galkina Elena; Mingaleva Ekaterina (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001